Vernet Syndrome and peripheral vertigo syndrome: 2 jugulotympanic paragangliomas case reports - Veloso-Teles, Rafaela (2014)
Introduction: Jugulotympanic Paragangliomas are uncommon tumors, mostly manifested by unilateral transmission hearing loss and pulsatile tinnitus. Frequently, they are detected in advanced stage due to its progressive growth, unspecific and diverse clinical symptoms. Case report: We report two cases of Jugulotympanic Paragangliomas diagnosed and studied in the ENT outpatient clinic of our hospital. The first patient was referred due to dysphonia and presented with right palsy of the IX, X and XI cranial nerves (Vernet Syndrome), and red mass visible through the inferior tympanic membrane quadrants on right otoscopy. The second patient was referred with vertigo, unilateral tinnitus and neurosensorial hearing loss, and the otoscopy revealed a right pulsatile mass in the middle ear. Discussion: These tumors have different manifestations and their basic investigations should include audiometric evaluation, imaging tools such as computed tomography and magnetic resonance imaging, and catecholamine metabolites dosage. The arteriography can be used in the diagnosis and pre-operative embolization. Treatment is planned on a case-by-case basis, and it can be more conservative (wait and scan) or more interventive with surgery, radiotherapy and, more recently, radiosurgery. Conclusion: Multidisciplinary collaboration in the management, treatment and follow-up of these patients is essential. Glomus tumor treatment is a challenge; we will have to wait for long term studies about radiosurgery results and future directions towards gene manipulation in familiar cases.